2016
DOI: 10.1097/ccm.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Perihematomal Edema Expansion Predicts Outcome After Intracerebral Hemorrhage

Abstract: Objective Intracerebral hemorrhage (ICH) is a devastating disorder with no current treatment. Whether peri-hematomal edema (PHE) is an independent predictor of neurologic outcome is controversial. We sought to determine whether PHE expansion rate predicts outcome after ICH. Design Retrospective cohort study Setting Tertiary medical center Patients 139 consecutive supratentorial spontaneous ICH patients >18 years admitted between 2000–2013. Interventions None Measurements and Main Results ICH, intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 32 publications
1
102
3
1
Order By: Relevance
“…7 In a single-centre cohort in which participants with significant intraventricular haemorrhage and warfarin-related ICH were excluded, we reported that PHE growth rate at 24 hours was independently associated with death or disability. 8 However, at 72 hours, PHE growth rate correlated with functional outcome but not with mortality. 8 This may have been due to the small sample size of the study that limited the power to detect a significant association.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…7 In a single-centre cohort in which participants with significant intraventricular haemorrhage and warfarin-related ICH were excluded, we reported that PHE growth rate at 24 hours was independently associated with death or disability. 8 However, at 72 hours, PHE growth rate correlated with functional outcome but not with mortality. 8 This may have been due to the small sample size of the study that limited the power to detect a significant association.…”
Section: Introductionmentioning
confidence: 94%
“…8 However, at 72 hours, PHE growth rate correlated with functional outcome but not with mortality. 8 This may have been due to the small sample size of the study that limited the power to detect a significant association. These results need to be replicated in a large multicentre cohort that has greater external validity.…”
Section: Introductionmentioning
confidence: 94%
“…Recent work has demonstrated an accurate and reproducible method for measuring PHE from computed tomography (CT) [10], as well as evidence that PHE expansion rate from admission to 24 or 72 hours post-ICH independently predicts 90-day mortality and functional outcome [11]. The objective of this analysis was to determine whether PHE expansion rate is associated with outcome for both deep and lobar ICH and, if so, whether its effect varies depending on the site of hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, rate of perihematomal edema expansion at 24 hours predicted a higher mortality (odds ratio 2.97) and poor modified Rankin Scale scores (odds ratio 2.21) at 90 days. 11 Intensive BP lowering within the first 24 hours after the onset of ICH has been shown to reduce cerebral edema and perihematomal edema, leading to better outcomes. 12 First day mean arterial pressure (MAP) is directly linked to the chance of survival.…”
Section: Effects Of Hypertension On Acute Ichmentioning
confidence: 99%